Hemoglobinas del recién nacido. - Notti, Humberto J.; Lentini, José; del Pont, Oscar Marco; Ampuero, Pedro A.; de la Rosa de Ampuero, Sara I. (Revista Cubana de Pediatría, 2022)
Determinar resultados de hemoglobinas en recién nacidos.